Validity of Electronic Signatures of The Notary and The Parties on The Notary Deed - Fahryan, Ahmad; Setyawati, Setyawati; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
The development of information technology has driven the transformation of notarial practices, including the implementation of electronic signatures, which are generally recognized as having legal force under the Electronic Information and Transactions Law (UU ITE). However, the Notary Law (UUJN) has not explicitly regulated the use of electronic signatures in the creation of authentic deeds, thus still requiring the physical presence of the parties. This has given rise to debate regarding the validity of electronic notarial deeds. This study aims to analyze the validity of electronic signatures of notaries and parties in notarial deeds. The method used is a normative juridical approach through a literature review, with analytical descriptive research specifications that systematically and comprehensively explain the related legal issues. The results of the study indicate that legally, electronic signatures are valid in electronic transactions, but their application in notarial deeds is still limited due to exceptions in Article 5 paragraph (4) of the ITE Law, legal constraints in the UUJN, digital security issues, and differences in legal understanding. Therefore, harmonization of regulations, strengthening digital infrastructure, and improving notary competency are important steps to ensure that electronic notarial deeds continue to have legal certainty and adequate legal protection.